Analisis Pengaruh Tingkat Suku Bunga, Nilai Tukar, Dan Performa Ekonomi Terhadap Pendalaman Sektor Keuangan (Financial Deepening) Di Indonesia Periode 2006.Q1-2015.Q4 - Malinda, Setyayunda Putri (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to examine the interest rate, exchange rate, and economic’s performance that affect the financial deepening on Indonesia economy for 2006-2015 by using multiple linier regression. This research used the time series data that quartally formed for 2006.Q1- 2015.Q4. Methode of analysis was ordinary least square (OLS) with the E-views software for examine the research data. The results of the analysis for this model shows that interest rate, exchange rate, and economic’s performance were significantlly effecting the financial deepening. The implication of this study is expected to help the government and the authority of monetary evaluate the financial deepening policy for stimulate the economic growth and development.Keywords: Interest rate, exchange rate, economic’s performance, financial deepening